2016
DOI: 10.1111/pce.12787
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between temperature and intercellular CO2 concentration in controlling leaf isoprene emission rates

Abstract: Plant isoprene emissions have been linked to several reaction pathways involved in atmospheric photochemistry. Evidence exists from a limited set of past observations that isoprene emission rate (I ) decreases as a function of increasing atmospheric CO concentration, and that increased temperature suppresses the CO effect. We studied interactions between intercellular CO concentration (C ) and temperature as they affect I in field-grown hybrid poplar trees in one of the warmest climates on earth - the Sonoran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 54 publications
3
32
1
Order By: Relevance
“…In our experiment, a significantly reduced isoprene emission rate under [ enriched O 3 ] was observed for Q. mongolica, and Ci under [ enriched O 3 ] was significantly higher than that in the other two treatments. This result is consistent with those of the abovementioned studies of Yuan et al 2016 andMonson et al 2016 . However, we did not see a significantly lower DMAPP content in the two species during July and September.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our experiment, a significantly reduced isoprene emission rate under [ enriched O 3 ] was observed for Q. mongolica, and Ci under [ enriched O 3 ] was significantly higher than that in the other two treatments. This result is consistent with those of the abovementioned studies of Yuan et al 2016 andMonson et al 2016 . However, we did not see a significantly lower DMAPP content in the two species during July and September.…”
Section: Discussionsupporting
confidence: 83%
“…Yuan et al 2016 speculated that higher Ci due to the reduced photosynthetic rate under [ enriched O 3 ] might decrease the availability of phosphoenolpyruvate PEP for isoprene synthesis. Monson et al 2016 obtained an A-Ci curve for field-grown poplar at ambient O 3 levels and showed that the isoprene emission rate decreased with an increase in Ci at 25 C. The authors attributed the cause to a decreased pool size of DMAPP with the increase in Ci. As evidence for this hypothesis, the DMAPP content was observed to be lower under [ enriched O 3 ] than under the control in the aspen FACE experiment Calfapietra et al, 2008 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Niinemets and Sun , Monson et al. ). If the current physiological mechanistic models are correct, then elevated CO 2 will not suppress isoprene emissions under high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated CO 2 inhibits leaf-level isoprene emissions when temperatures are not elevated (Sharkey et al 1991, Sharkey andMonson 2014). Recent work, however, has shown that this CO 2 -caused reduction in isoprene emission disappears under higher temperatures and has presented convincing evidence for the mechanism underlying the temperature dependency of the CO 2 suppression (Sun et al 2013, Potosnak et al 2014, Niinemets and Sun 2015, Monson et al 2016). If the current physiological mechanistic models are correct, then elevated CO 2 will not suppress isoprene emissions under high temperatures.…”
Section: Uncertaintiesmentioning
confidence: 99%